Procedencia de la acción de habeas corpus en los casos de privación de la libertad - Solano Pauta, Carlos Yasmany (Machala : Universidad Técnica de Machala., 2018)
El presente trabajo de investigación tiene como objeto central a la acción de habeas corpus, garantía jurisdiccional de los derechos de las personas reconocidos en la Constitución y en los tratados sobre Derechos Humanos. Se partió de un caso propuesto a fin de identificar el mecanismo constitucional adecuado a fin de precautelar lo que el accionante consideraba una detención arbitraria e ilegal. De esta manera el objetivo principal de la investigación fue el de determinar si en el caso propuesto, la retención de una persona en un centro de tratamiento de adicciones viola el principio de libertad y movilidad personal.
The main purpose of this research work is habeas corpus, a jurisdictional guarantee of the rights of persons recognized in the Constitution and in human rights treaties. It was based on a proposed case in order to identify the appropriate constitutional mechanism in order to protect what the plaintiff considered an arbitrary and illegal detention. In this way, the main objective of the investigation was to determine if in the proposed case, the retention of a person in an addiction treatment center violates the principle of freedom and personal mobility. In the concrete fact, the relatives of a person locked up against their will in a treatment center for addictions, this with the idea of helping him to overcome his condition. This confinement, in a hypothesis, constitutes a retention that harms the right to freedom and personal mobility, for more good intentions that the relatives and the holders of the Center have had.
Keywords: ILEGITIMA; ARBITRARIA